3D numerical investigation of the detonation wave propagation influence on the triangular plate deformation using finite rate chemistry model of LS-DYNA CESE method. (March 2022) - Haghgoo, Mojtaba; Babaei, Hashem; Mostofi, Tohid Mirzababaie
Highlights: This numerical simulation predicts the damage mode, large deformation, and thinning of plate as a function of the intensity of detonation load. The numerical simulation results demonstrated a good agreement compared with experimental data. The results illustrated that the velocity of plate was highly dependent on the ignition point location. Numerical simulation revealed that the structural response transformed from yield to ripping failure near plate edges. Abstract: In this article, an immersed boundary method which couples a Lagrangian structure solver with an Eulerian fluid solver with a chemistry model capable of detonation computation for H2 O2 is developed to achieve the fluid-structure interaction, the deformation, and the damage of a thin plate subjected to a gaseous detonation loading. The Johnson-Cook material model was used for the plate which incorporates strain hardening, temperature softening, and strain rate effects. The detonation wave is modeled using LS-DYNA finite rate chemistry model incorporated in conservative element solution element solver. Other objectives of this numerical simulation such as estimation of deflection and stress state failure mechanism of material at high strain rate were derived based on a strain-rate dependent failure criterion. The simulated deformation pattern and the effect of pre-detonation pressure are compared with experimental results and a good agreement was acquired. Further additional simulations revealed that the pre-detonation pressure, ignition point location, and longitudinal capacity of the cylinder have great influences on the deformation and sensed pressure of the plate. Graphical abstract: Image, graphical abstract